2003
DOI: 10.1042/bj20030825
|View full text |Cite
|
Sign up to set email alerts
|

A role for calcium in the regulation of neutral trehalase activity in the fission yeast Schizosaccharomyces pombe

Abstract: Neutral trehalases mobilize trehalose accumulated by fungal cells as a protective and storage carbohydrate. A structural feature of these enzymes is the presence of an EF-like motif similar to that shown by many Ca2+-binding proteins. In this study we provide direct evidence for physical binding of Ca2+ to neutral trehalase (Ntp1p) of the fission yeast Schizosaccharomyces pombe, and show that aspartic residues at positions 97 and 108 in the conserved putative Ca2+-binding motif of Ntp1p appear to be responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The N-terminal part of S. cerevisiae contains sequence that closely resembles such an EF-hand motif (Fig. 1), suggesting the possibility that this sequence and the calcium binding play a role in the regulation of this enzyme activity (13). In this work, various techniques of structural biology, including HDX- a The C␣-C␣ interresidue distance constraints used were based on the length of the spacer arm, which is 7.7 Å for DSG and 11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal part of S. cerevisiae contains sequence that closely resembles such an EF-hand motif (Fig. 1), suggesting the possibility that this sequence and the calcium binding play a role in the regulation of this enzyme activity (13). In this work, various techniques of structural biology, including HDX- a The C␣-C␣ interresidue distance constraints used were based on the length of the spacer arm, which is 7.7 Å for DSG and 11.…”
Section: Discussionmentioning
confidence: 99%
“…Franco et al (13) showed that the Ca 2ϩ -dependent activation of Nth1 from Schizosaccharomyces pombe is mediated by a conserved Ca 2ϩ -binding EF-hand-like motif that is also present in S. cerevisiae Nth1 (sequence 114 DTDKNYQITIED 125 ). To investigate the importance of this motif in S. cerevisiae pNth1 activation, we performed site-directed mutagenesis of several residues that correspond to both conserved and non-conserved positions from EF-hand motifs of numerous Ca 2ϩ -binding proteins (Fig.…”
Section: The Integrity Of the Ef-hand-like Motif-containing Region Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mass spectrometry evidence was reported for phosphorylation of purified trehalase by PKA in vitro on Ser 20 , Ser 21 , Ser 60 , and Ser 83 (24). Schizosaccharomyces pombe neutral trehalase has a structure similar to that of S. cerevisiae trehalase and is rapidly activated under similar environmental conditions (25, 26). Mutagenesis of the putative PKA phosphorylation sites resulted in inactive trehalases unresponsive to environmental stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with trehalases from prokaryotic and higher eukaryotic organisms, yeast neutral trehalases possess an N-terminal extension that contains four cAMP-dependent protein kinase (PKA) phosphorylation sites (S20, S21, S60, and S83 in Saccharomyces cerevisiae Nth1) and the calcium-binding EF-hand-like motif (Fig. 1A), indicating significantly different regulation (17)(18)(19). It was subsequently shown that S. cerevisiae Nth1 is indeed activated in a PKA-and calcium-dependent manner in a process that requires interaction with the 14-3-3 protein through motifs containing phosphoserines pS60 and pS83 (20)(21)(22)(23).…”
mentioning
confidence: 99%